Additive decompositions with interaction effects - Martin Biewen (Institute for the Study of Labor (IZA), 2012)
This paper proposes a comprehensive, path-independent decomposition formula of changes into ceteris paribus effects and interaction effects. The formula implies a reassessment of sequential decomposition methods that are widely used in the literature and that are restrictive in how they treat interaction effects. If counterfactual outcomes are correctly specified, it may also be viewed as a description of certain aspects of causality in the situation where more than one causal influence is present.
Keywords: J31; J71; C02; D31; 330; ceteris paribus effects; interaction effects; Oaxaca-Blinder decomposition; Dekompositionsverfahren; Theorie